PENGARUH GAYA HIDUP, KEPERCAYAAN, DAN KEMUDAHAN TERHADAP KEPUTUSAN BERBELANJA ONLINE MELALUI SHOPEE PADA MASYARAKAT KOTA SEMARANG - Prasetyawan, Adrian (Jurnal Pijar, 2024)
In Indonesia, digital money is spreading rapidly, and financial technology is also developing at the same time. The use of e-commerce from all circles has expanded due to the rapid growth of digitalization. Shopee is one of the e-commerce platforms that is in demand by the public. Shopee is a preferred online shopping choice because of its visually appealing application display. The majority of Indonesian people, especially in Semarang City, use Shopee for shopping. The purpose of this study was to determine how Semarang City residents' decisions about online purchases at Shopee are influenced by factors such as ease of use, trust, and lifestyle. This study is a quantitative study and uses a purposive sampling technique. The results of the reliability test were obtained using Cronbach alpha (α) and the results of the validity test were obtained using the KMO test tool. The research instrument was used to obtain data on multiple regression coefficients, determination coefficients (R2), F tests, and t tests. The research findings show that people in Semarang City make significant judgments about what to buy at Shopee based on factors including ease of use, trust, and lifestyle